2018
DOI: 10.1021/acs.energyfuels.8b01129
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Reversible Absorption of CO2 by Functional Deep Eutectic Solvents

Abstract: Extremely low-volatility functional deep eutectic solvents (DESs), based on ethylene glycol (EG) and diethylene glycol (DG) as hydrogen-bond donor and the ammonium salts obtained from triethylenetetramine (TETA) and HCl at different mole ratios as hydrogen-bond acceptor, were designed and used to capture CO2. All of the designed DESs can efficiently capture CO2 even at low partial pressures. CO2 absorption capacity of [TETA]­Cl-EG DES with n [TETA]Cl/n EG 1:3 is high up to 17.5 wt % (1.456 mol CO2/mol [TETA]­C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 30 publications
1
49
0
1
Order By: Relevance
“…Due to the chemisorption occurring in DESs used in this study, the CO 2 uptake was much higher than in DESs as physical absorbents, such as for example tetrabutylammonium bromide coupled with methyldiethanol that was studied by Haider and gave a capacity of 0.29 moleCO 2 /mole solvent at high pressure of 1 MPa and 303.15 K [22]. [26]. However, for MEA in the role of HBD and choline chloride, tetraethylammonium chloride and tetramethylammonium chloride as HBA, Zhuo et al reported increasing CO 2 absorption from 1:2 up to 1:6.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Due to the chemisorption occurring in DESs used in this study, the CO 2 uptake was much higher than in DESs as physical absorbents, such as for example tetrabutylammonium bromide coupled with methyldiethanol that was studied by Haider and gave a capacity of 0.29 moleCO 2 /mole solvent at high pressure of 1 MPa and 303.15 K [22]. [26]. However, for MEA in the role of HBD and choline chloride, tetraethylammonium chloride and tetramethylammonium chloride as HBA, Zhuo et al reported increasing CO 2 absorption from 1:2 up to 1:6.…”
Section: Resultsmentioning
confidence: 94%
“…CO 2 uptake in different DESs of 1:4 molar ratio.Literature describes the cases where the CO 2 absorption trend varies depending on the HBD and HBA ratio. For example, Zhang et al conducted research on absorption in tetraethylenetetramine chloride [TETEA.Cl] and ethylene glycol [EG] or diethylene glycol[DG] and discovered that the CO 2 capacity for [TETEA.Cl][DG] increases from 1:1 to 1:2 and then decreases up to 1:7 and for [TETEA.Cl][EG] increases from 1:1 to 1:3 and further decreases[26]. However, for MEA in the role of HBD and choline chloride, tetraethylammonium chloride and tetramethylammonium chloride as HBA, Zhuo et al reported increasing CO 2 absorption from 1:2 up to 1:6.…”
mentioning
confidence: 99%
“…As aminas reagem com o CO 2 através da formação do (ou derivado do) ácido carbâmico ou do sal de carbamato -RR´NCOOe/ou carbonatos na presença de água [54]. Esta abordagem foi aplicada nos líquidos iónicos [55], hidrogéis [56], polímeros porosos [57][58][59], materiais inorgânicos como a sílica (dióxido de silício) [60] ou óxidos metálicos [61], estruturas metal-orgânicas (MOFs, Metal Organic Frameworks) [62], estruturas orgânicas covalentes (COFs, Covalent Organic Frameworks) [63] e também em DES [64][65][66][67][68]. Por exemplo, Trivedi et al [64] produziram um DES, [MEA•Cl][EDA] (1:3) (Figura 4) que proporcionou uma grande capacidade de captura de CO 2 em massa (31,5% ou 0,54 moles de CO 2 por mol de solvente a 1 bar e 303 K).…”
Section: Sistemaunclassified
“…As an alternative, DESs not only have similar properties to ionic liquids, but also have many other advantages, including simple preparation, cheap raw materials, low toxicity, biodegradability and no further purication. 27 Because of these properties, DESs have gradually become a new type of green solvents and catalysts, and have been widely used in biocatalysis, 28,29 extraction, 30,31 carbon dioxide capture, [32][33][34] biomedical applications, 35 material synthesis [36][37][38] and other elds. In recent decades, DESs as a reaction medium have attracted widespread attention, making them have broad application prospects in industrial production.…”
Section: Introductionmentioning
confidence: 99%